2007
DOI: 10.1590/s0036-46652007000500007
|View full text |Cite
|
Sign up to set email alerts
|

Affinity and diversity indices for anopheline immature forms

Abstract: As for the entire Amazon Region, malaria continues to be a major health public problem in Roraima that presented an Annual Parasitic Index of 85.4 in 2005, the highest in Brazil. Information on anopheline breeding sites is an essential component in malaria control strategies. Aiming to contribute to the limited knowledge on anopheline immature forms in Roraima, collections and breeding site observations were performed in 10 breeding sites around the capital city Boa Vista. Collections were carried out in the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 11 publications
3
26
0
Order By: Relevance
“…24,25 The preference of A. darlingi for sites with lower luminosity may help explain the absence of the species in deforested areas, as well as in the largely treeless savanna in Suriname, 26 English Guyana, 27 and in northern Roraima. 16,28 The species reappears in patches of forests and alluvial forests. 16 The preference for lower luminosity has been suggested to be a behavioral characteristic of the forest-adapted ovipositing female.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 The preference of A. darlingi for sites with lower luminosity may help explain the absence of the species in deforested areas, as well as in the largely treeless savanna in Suriname, 26 English Guyana, 27 and in northern Roraima. 16,28 The species reappears in patches of forests and alluvial forests. 16 The preference for lower luminosity has been suggested to be a behavioral characteristic of the forest-adapted ovipositing female.…”
Section: Discussionmentioning
confidence: 99%
“…In 2005, several immature specimens of malaria vectors were described in areas surrounding Boa Vista, especially in the dry season, but anopheles darling larvae were found rarely. The authors discuss the usual persistence of malaria transmission even under these conditions (Nagm et al 2007). Another study showed the impact of human settlements and other anthropogenic changes on the environment and how climate variability affected both population density and relative abundance of these vectors (Gomes et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…goeldii) has been described as a species readily able to colonize and dominate in altered environments 33 as a result of its ability to survive in a variety of conditions, such as sunlit or shaded sites, fresh, clear, still, or flowing water 34 and occasionally in turbid and polluted sites. 35 The Albitarsis complex consists of at least eight species and a new lineage 36,37 ; only some of these have been incriminated as malaria vectors. The medical importance of Anopheles oryzalimnetes (Wilkerson and Motoki), previously Anopheles albitarsis B, is largely unknown, although this species has been attracted to human bait.…”
Section: Introductionmentioning
confidence: 99%